The lower–middle Viséan boundary interval in the Palaeotethys: refinements for the foraminiferal zonal schemes. (30th March 2020) - Cózar, Pedro; Vachard, Daniel; Somerville, Ian D.; Izart, Alain; Coronado, Ismael
Abstract: A new foraminiferal subzone (Cf5α or MFZ12α) in between the classical foraminiferal zonal biozones is characterized by the first occurrence of Archaediscus at concavus stage, primitive species of Pojarkovella, as well as the first Endothyranopsis s.s. This interval is represented in England, France and Morocco (in the western Palaeotethys) and in South China, and more widely in Iran (in the eastern Palaeotethys), where it is partly similar to the MFZ11B subzone defined by previous authors. The position of this new biozone within the Livian or Holkerian substages suggests that it has to be considered as part of the middle Viséan substage. We therefore propose the abandonment of the notation MFZ11B, which includes lower Viséan rocks, and the subdivision of the middle Viséan zones MFZ12 and Cf5 into two subzones MFZ12α or Cf5α, and MFZ12β or Cf5β, with the latter subzone containing the classical Livian–Holkerian foraminiferal guides Pojarkovella nibelis and Koskinotextularia . Furthermore, the lower Viséan MFZ11 zone can be subdivided in most Palaeotethyan basins into three subzones: a lower MFZ11α subzone (characterized by the first occurrence of Uralodiscus rotundus, as well as most species of Glomodiscus ); a middle MFZ11β subzone (characterized by the first occurrence of Archaediscus at involutus stage and Conilidiscus ); and an upper MFZ11γ subzone (characterized by the first occurrence of Nodosarchaediscus, Consobrinellopsis and Lituotubella ).